Asset building & community development - Green, Gary Paul.; Haines, Anna. (New Delhi, 2016)
Examines the promise and limits of community development by showing students and practitioners how asset-based developments can improve the sustainability and quality of life. Authors Gary Paul Green and Anna Haines provide an engaging, thought-provoking, and comprehensive approach to asset building by focusing on the role of different forms of community capital in the development process. Updated throughout, this text explores how communities are building on their key assets?physical, human, social, financial, environmental, political, and cultural capital? to generate positive change. With a focus on community outcomes, the authors illustrate how development controlled by community-based organizations provides a better match between assets and the needs of the community.
Keywords: Social Science